2014
DOI: 10.4049/jimmunol.1302119
|View full text |Cite
|
Sign up to set email alerts
|

Tetraacylated Lipid A and Paclitaxel-Selective Activation of TLR4/MD-2 Conferred through Hydrophobic Interactions

Abstract: LPS exerts potent immunostimulatory effects through activation of the TLR4/MD-2 receptor complex. The hexaacylated lipid A is an agonist of mouse (mTLR4) and human TLR4/MD-2, whereas the tetraacylated lipid IVa and paclitaxel activate only mTLR4/MD-2 and antagonize activation of the human receptor complex. Hydrophobic mutants of TLR4 or MD-2 were used to investigate activation of human embryonic kidney 293 cells by different TLR4 agonists. We show that each of the hydrophobic residues F438 and F461, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Similar to Resman et al (7,8), we observed species-specific differences in the ability of human and mouse TLR4 mutants to respond to E. coli LPS and lipid IVA. F440A or F463A mutation of human TLR4 caused a more severe phenotype: the complete or near-complete loss in the ability to activate NFB in response to both E. coli LPS and lipid IVA, whereas F438A or F461A mutants of mouse TLR4 could still partially respond to E. coli LPS (Fig.…”
Section: Volume 290 • Number 21 • May 22 2015supporting
confidence: 71%
See 1 more Smart Citation
“…Similar to Resman et al (7,8), we observed species-specific differences in the ability of human and mouse TLR4 mutants to respond to E. coli LPS and lipid IVA. F440A or F463A mutation of human TLR4 caused a more severe phenotype: the complete or near-complete loss in the ability to activate NFB in response to both E. coli LPS and lipid IVA, whereas F438A or F461A mutants of mouse TLR4 could still partially respond to E. coli LPS (Fig.…”
Section: Volume 290 • Number 21 • May 22 2015supporting
confidence: 71%
“…Additionally, because one of the acyl chains on hexa-acylated E. coli lipid A sticks out of the pocket and lies on the surface of MD-2, this also promotes dimerization via interaction with uncharged amino acids in TLR4* (4,5). Uncharged amino acids in TLR4* (Phe-440 and Phe-463 in human TLR4 and Phe-438, Phe-461 in mouse TLR4) have also been proposed to engage MD-2 and support receptor activation (5,7,8).…”
mentioning
confidence: 99%
“…17) To investigate the antagonizing effect of HSYA on the specific receptor binding LPS, we used a human lung epithelial cell line (A549) and human umbilical vein cell line (Eahy926). Alveolar epithelial cells and capillary endothelial cells are the two most common cells in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…2014,2008). Up to now most mutants of MD-2 closely followed this lipid IVa/taxol specificity, however we recently characterized a mutation of murine MD-2 (mMD-2) that retains strong activation by lipid IVa yet is no longer activated by taxol (Resman et al, 2014).…”
Section: Lps Featurementioning
confidence: 98%